Understanding Exponents
3
4
3
4
3 x 3 x 3 x 3
81
Multiply 3x3x3x3 = 81
3 1 3
3
3
4
3
2
How would you write this problem
using exponents?
1. 2 • 2 • 2 • 2 • 2 • 2 • 2 =
2. (-3)(-3) (-3)(-3) =
3. a • a • a • a •...
How would you write this problem
using exponents?
1. 2 • 2 • 2 • 2 • 2 • 2 • 2 =
2. (-3)(-3) (-3)(-3) =
3. a • a • a • a •...
1. 4( 3 + 2)2
=
2. 2 • 52
+ 4 • (-3)=
3. 2x3
+ 4y (for x = -2 ; y = 3)
4. 3(a)2
+ 6 (for a = 5)
5. -a4
(for a = 2)
6. (-a)...
1. 4( 3 + 2)2
=
2. 2 • 52
+ 4 • (-3)=
3. 2x3
+ 4y (x = -2 ; y = 3)
4. 3(a)2
+ 6 ( a = 5)
5. -a4
(a = 2)
6. (-a)4
(a = 2)
4...
1. 4( 3 + 2)2
=
2. 2 • 52
+ 4 • (-3)=
3. 2x3
+ 4y (x = -2 ; y = 3)
4. 3(a)2
+ 6 ( a = 5)
5. -a4
(a = 2)
6. (-a)4
(a = 2)
4...
Upcoming SlideShare
Loading in …5
×

Understanding exponents

796 views
681 views

Published on

Understanding exponents

Published in: Education, Technology
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
796
On SlideShare
0
From Embeds
0
Number of Embeds
28
Actions
Shares
0
Downloads
3
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Understanding exponents

  1. 1. Understanding Exponents 3 4
  2. 2. 3 4 3 x 3 x 3 x 3 81 Multiply 3x3x3x3 = 81 3 1 3 3 3 4 3 2
  3. 3. How would you write this problem using exponents? 1. 2 • 2 • 2 • 2 • 2 • 2 • 2 = 2. (-3)(-3) (-3)(-3) = 3. a • a • a • a • a • a • a • a = 4. a • m • m • a • m • a • a = 5. p • 2 • r • r • r • p • 2 =
  4. 4. How would you write this problem using exponents? 1. 2 • 2 • 2 • 2 • 2 • 2 • 2 = 2. (-3)(-3) (-3)(-3) = 3. a • a • a • a • a • a • a • a = 4. a • m • m • a • m • a • a = 5. p • 2 • r • r • r • p • 2 = 27 (-3)4 a8 a4 m3 22 p2 r3
  5. 5. 1. 4( 3 + 2)2 = 2. 2 • 52 + 4 • (-3)= 3. 2x3 + 4y (for x = -2 ; y = 3) 4. 3(a)2 + 6 (for a = 5) 5. -a4 (for a = 2) 6. (-a)4 (for a = 2)
  6. 6. 1. 4( 3 + 2)2 = 2. 2 • 52 + 4 • (-3)= 3. 2x3 + 4y (x = -2 ; y = 3) 4. 3(a)2 + 6 ( a = 5) 5. -a4 (a = 2) 6. (-a)4 (a = 2) 4(5)2 4(5•5) 4(25) =100 -62 192 81 -16 16
  7. 7. 1. 4( 3 + 2)2 = 2. 2 • 52 + 4 • (-3)= 3. 2x3 + 4y (x = -2 ; y = 3) 4. 3(a)2 + 6 ( a = 5) 5. -a4 (a = 2) 6. (-a)4 (a = 2) 4(5)2 4(5•5) 4(25) =100 -62 192 81 -16 16

×